Strategies for an Innovative Drug Maker to Retain its First-Mover Advantage when faced with Patent Expiry and impending Generic Competition - Mohandas, Abhilasha (2011)
An innovative pharmaceutical company is known to enjoy a First-Mover Advantage when it launches a patented drug in the market. However, research suggests that the edge diminishes with time. With a major patent cliff round the corner, originators are in dire need of some way to retain their once acquired FMA.